Hemolysis Detection in Sub-Microliter Volumes of Blood Plasma - Azhar, Mohiudeen; Galgalkar, Sudipa; Chakraborty, Ishita; Mehta, Kalpesh; Ragavender, M.S.; Prabhu, Vishal; Ledden, David (IEEE transactions on biomedical engineering, 2020)
Objective: Hemolysis is one of the main reasons for blood sample rejection in clinical laboratories. The scope of this study is to develop a simple, sensitive, and cost-effective method for hemolysis detection in presence of interferents like bilirubin, and lipids in sub-microliter volumes of blood plasma. Methods: Experimental samples were prepared in plasma extracted from whole blood. These samples were typically mixtures of hemoglobin, bilirubin, and lipids of varying concentrations. A multispectral optical setup was devised to probe these samples without any optical filters or moving parts. Results: The hemoglobin content in the samples were measured within the range of 0 mg/dL to 400 mg/dL concentration using <; 1 μL of detection volume. Detection sensitivity of >90% accuracy and ~10% coefficient of variation across 27 unknown samples. The optical attenuation path length used was merely ~150 micrometers. The spectral interference due to overlapping absorption spectrum of bilirubin and scattering spectrum of lipids are resolved using linear matrix algebra algorithms. Conclusion: Hemolysis can lead to spurious measurements of key clinical parameters such as Potassium, Lactate Dehydrogenase, Aspartic Acid Transferase, and other diagnostic biomarkers. Commonly used visual inspection of blood plasma coloration is prone to variability. Description of the sample preparation, calibration and verification of the experimental setup and linear matrix algebra algorithm for analyte interference determination is reported here. Significance: Owing to the sub-microliter detection volume and high sensitivity, the system has realistic potential to be implemented in point of care medical devices that demands such low volumes of clinical specimen.